PENGARUH KERAGAMAN PRODUK DAN CITRA MEREK TERHADAP MINAT BELI ES KRIM AICE DI KABUPATEN KARAWANG - Afifah Rozaana; Ina Ratnasari (MANAJEMEN DEWANTARA, 2023)
The food sector is a business sector that is experiencing an increase in Indonesia, one of which is ice cream. Aice is committed to making creative and innovative breakthroughs by launching variants of unique flavors and shapes as well as very friendly prices for consumers. Product diversity and brand image can increase purchase intention. This study aims to examine and analyze the Effect of Product Diversity and Brand Image on Interest in Buying Aice Ice Cream in Karawang Regency.This research was conducted using quantitative methods with descriptive and verification approaches. The population in this study is the community in Karawang Regency with a sample of 384 respondents calculated using the Issac Michael formula and an error rate of 5% and non-probability sampling technique with a purposive sampling approach. The data analysis technique used is path analysis with SPSS 21 software tools.The results showed that product diversity, brand image, and interest in buying Aice ice cream in Karawang Regency were considered good by the respondents of this study. Product diversity and brand image have a positive and significant effect on buying interest. This shows that the diversity of products and brand image owned by Aice ice cream makes respondents interested so that it can increase consumer buying interest.